Zegarki Tyszkiewiczów. Część druga - Zieliński, Jan (Załącznik Kulturoznawczy, 2024)
Second part of a paper; the first one was published in “Załącznik Kulturoznawczy” 2020 No 2. This part, in opposition to the previous one, concentrates on watches and other technical devices in one novel, written by a female member of the Tyszkiewicz family, Maria Tyszkiewiczówna (1871-1943). The novel, entitled Spójnik (A Conjunction), was published in Warsaw in 1902. It’s critical reception was rather moderate in Poland, but quite favorable abroad. The paper discusses different types of watches, present in this novel, and the role they play in the development of the plot. Tyszkiewczówna’s novel contains also probably the first detailed description of a phonograph in Polish literature. It’s author develops a vision of future phonographic archives, preserving human voices from different periods. She is interested in technical devices that convey idealistic notions (general, like time, or individual, like thoughts), through the means of the acoustic waves.